Moldova : Arena of International Influences. - Kosienkowski, Marcin (Lexington Books, 2012)
Moldova: Arena of International Influences assembles twenty-one Moldova experts and practitioners of a different nationalities, each describing his or her own country's contemporary foreign policy in this Eastern European country. More than just a map of the international political landscape in Moldova today, the volume provides a unique international perspective of the country's future. An essential reference for scholars and policy makers themselves interested in stepping into the Moldovan arena. </sp.